Assessment of Food Security Situation among Farming Households in Rural Areas of Kano State, Nigeria - Irohibe Ifeoma; Agwu Agwu (Journal of Central European Agriculture, 2014)
Achieving food security is still a major problem for households in most rural areas of Nigeria. This study was therefore designed to assess the food security status among farming households in rural areas of Kano state, Nigeria. The study utilized a multistage random sampling technique to +select a sample of 120 rural farm households for interview. Data collected were analysed using percentages, mean score, logistic regression and food security index. Using the food security index approach, the study revealed that 74% of the respondents were food secure while 26% were food insecure. The results of the logistic regression revealed that educational level (p0.05; z = 1.95), sex (p0.05; z = 1.99), household size (p0.05; -4.29) and access to credit (p0.05; z = 2.4) were significant determinants of food security. Also, the major effect of food insecurity on the households include reduction in household income/ savings due to increased expenditure on food (M= 3.58), among others. The perceived coping strategies in cushioning the effects of food insecurity include engaging in off-farm and non-farm jobs to increase household income, (M= 2.77), among others. The study therefore recommends the fast tracking of already established policy measures aimed at reducing food insecurity in the country. Also, efforts aimed at reducing food insecurity among rural farming households should focus on increasing household income and food supply.